IDENTIFIKASI AKAR MASALAH, PRAKTIK INOVATIF, DAN PENGUATAN BUDAYA BACA DAN NUMERASI - Sitti Nurpaida; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The literacy and numeracy crisis remains a major challenge in Indonesian primary education, as reflected in the results of the National Assessment and various educational studies. This study aims to examine the actual condition of students’ literacy and numeracy skills, identify the root causes of existing problems, and formulate recommendations for strengthening a contextual and sustainable literacy and numeracy culture at SD Negeri 19 Baba, Takalar Regency. This research employed a descriptive qualitative approach, with data collected through classroom observations, interviews with the principal, teachers, and parents, students’ literacy and numeracy assessments, document analysis, and student group discussions. The findings indicate that students’ literacy and numeracy skills are still at a level requiring improvement, particularly in reading comprehension and the application of numerical concepts in everyday contexts. The root causes include teacher-centered instructional practices, suboptimal use of learning media and reading corners, and inconsistent parental involvement. This study recommends strengthening literacy and numeracy through local-context-based learning, revitalizing reading corners and concrete learning media, implementing daily literacy and numeracy routines, and fostering sustainable collaboration between schools and parents.